Congenital cystic adenomatoid malformation, antenatal diagnosis: about one case - Adama, Dembélé; Issa, Ouédraogo; Sibraogo, Kiemtoré Sibraogo; Moussa, Bambara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Antenatal ultrasound screening of fetal malformations requires for management, the immediate nature of which at certain birth, conditions the survival of the newborn. The Objectives Describe a case of pulmonary cystic adenomatoid malformation discover during antenatal ultrasonography. It was a 36 years old primary patient, referred to the maternity of Lafontaine hospital (France) for the presence, on obstetrical ultrasound screening, of suspected lesions on the foetal right lung’s field in a 21 weeks gestation pregnancy. After successive obstetric ultrasound scan, it was discovered that the left lungs were big with some parenchymal cysts of different sizes more than 3 mm in diameter. We made a diagnosis of type I left pulmonary cyst adenoma with excess amniotic fluid, without associated anomalies. The pregnancy progressed to 40 weeks gestation and a caesarean section was done with extraction of a live female new born weighing 2730 gr. The new born had 40 days later a successful surgical lobectomy for a cystic adenomatoid dysplasia. Histological examination revealed type I Stocker congenital pulmonary cystic adenomatoid malformation. During obstetrical ultrasound screening, we paid more attention to the brain, the heart, the face. Through this study we realised that during routine antenatal ultrasound for morphology, we should also pay more attention to the lungs.